The Taste of Emotion: Metaphoric Association Between Taste Words and Emotion/Emotion-Laden Words - Zhou, Yanyun; Tse, Chi-Shing (Frontiers in Psychology, 2020)
According to the Conceptual Metaphor Theory, abstract concepts can be metaphorically associated with more concrete, physically embodied concepts, such as gustatory experience. Studies on taste-emotion metaphoric association reported that people associate love with sweet, jealousy with sour and bitter, and sadness with bitter. However, few studies have systematically examined the metaphoric association between taste and words referred to emotion (e.g., “sad”) or emotion-laden concepts (e.g., “funeral”). In the current four studies (total N=357), we examined this metaphoric association by having participants come up with a taste word when reading an emotion and emotion-laden word (Study 1—explicit association of taste words-to-emotion/emotion-laden words), come up with an emotion word when reading taste words (Study 2—explicit association of emotion words-to-taste words), rate the association between taste words and basic or non-basic emotion words (Study 3), and rate the association between taste words and a more expanded pool of emotion/emotion-laden words (Study 4). Results showed that sweet was mostly associated with positive emotion and emotion-laden words, whereas bitter, followed by sour and spicy, was mostly associated with negative emotion and emotion-laden words. The bidirectionality of taste-emotion metaphoric association was supported by our dataset. The implications of these findings on the Conceptual Metaphor Theory and embodied cognition are discussed.